2020
DOI: 10.1038/s41467-020-18782-1
|View full text |Cite
|
Sign up to set email alerts
|

TERMINAL FLOWER 1-FD complex target genes and competition with FLOWERING LOCUS T

Abstract: Plants monitor seasonal cues to optimize reproductive success by tuning onset of reproduction and inflorescence architecture. TERMINAL FLOWER 1 (TFL1) and FLOWERING LOCUS T (FT) and their orthologs antagonistically regulate these life history traits, yet their mechanism of action, antagonism and targets remain poorly understood. Here, we show that TFL1 is recruited to thousands of loci by the bZIP transcription factor FD. We identify the master regulator of floral fate, LEAFY (LFY) as a target under dual oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(166 citation statements)
references
References 128 publications
3
163
0
Order By: Relevance
“…[ 17 ] With the assistance of the bZIP transcription factor FD, TFL1 is recruited to the LFY chromatin and regulates LFY expression. [ 120,121 ] Conversely, AP1 and LFY repress TFL1 expression in the FM (Figure 4 and Table 2 ). [ 118,122,123 ] Loss‐of‐function mutants of both LFY and AP1 result in the transformation of flowers into inflorescence‐like shoots, whereas ectopic expression of LFY and AP1 causes early flowering and prematurely terminates inflorescence as a FM, largely because of the reduced expression of TFL1 .…”
Section: Molecular Mechanisms Underlying the Regulation Of Ft And Tfl1mentioning
confidence: 99%
“…[ 17 ] With the assistance of the bZIP transcription factor FD, TFL1 is recruited to the LFY chromatin and regulates LFY expression. [ 120,121 ] Conversely, AP1 and LFY repress TFL1 expression in the FM (Figure 4 and Table 2 ). [ 118,122,123 ] Loss‐of‐function mutants of both LFY and AP1 result in the transformation of flowers into inflorescence‐like shoots, whereas ectopic expression of LFY and AP1 causes early flowering and prematurely terminates inflorescence as a FM, largely because of the reduced expression of TFL1 .…”
Section: Molecular Mechanisms Underlying the Regulation Of Ft And Tfl1mentioning
confidence: 99%
“…While the organization of these regulatory networks at the shoot apex is currently unclear, further confirmation for this interplay between FD and ABA-related genes derives from ChIP and expression analyses of the shoot-specific TFL1 gene. The TFL1-FD complex directly represses, among others, the ABA biosynthetic gene ABA1 , the bZIPs ABF4 / AREB2 and ABI5 together with the ABI5 regulator AFP2 [ 27 ]. Thus, similar to floral targets, a competition between FT and TFL1 might modulate ABA levels or sensitivity in the shoot meristem cells ( Figure 1 ).…”
Section: Role Of Fd and Fd-like Bzips Protein Complexes In Modulatmentioning
confidence: 99%
“…The function of FT is antagonized by a structurally related protein, TERMINAL FLOWER 1 (TFL1), which is also mobile, albeit its range of movement appears to be limited to the shoot meristem cells [ 25 , 26 ]. TFL1 can interact with FD and is recruited via FD at thousands of genomic positions where it exerts transcriptional repression [ 27 , 28 ]. FT outcompetes TFL1 for FD binding and thus activates transcription of FD targets which include floral meristem identity genes, conferring a floral fate to newly arising lateral primordia, and hormone-related gene functions [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular analysis showed that FUL is upregulated in plants overexpressing SPL10 , indicating that FUL may function downstream of SPLs in mediating cauline leaf development [ 92 ]. The bZIP transcription factor FD interacts with both the flowering activator FLOWERING LOCUS T (FT) and the flowering repressor TERMINAL FLOWER1 (TFL1); these two complexes act antagonistically on a common set of targets, such as LFY , AP1 , and other flowering genes to induce flowering [ 93 , 94 , 95 ]. SPL3/SPL4/SPL5 interact with the floral activator FD to stimulate flowering under normal light conditions, and FAR-RED ELONGATED HYPOCOTYL3 and FAR-RED IMPAIRED RESPONSE1 prevent SPL3/SPL4/SPL5 activity in shady conditions to suppress flowering [ 96 , 97 ].…”
Section: Is Vegetative Phase Change a Prerequisite For Floral Indumentioning
confidence: 99%